Age‐related supportive care needs of women with gynaecological cancer: A qualitative exploration. (2nd May 2019) - Lopez, Anna‐Lena J.; Butow, Phyllis N.; Philp, Shannon; Hobbs, Kim; Phillips, Emily; Robertson, Rosalind; Juraskova, Ilona
Abstract: Women with gynaecological cancer (GC) experience significant morbidity with associated needs for support, not all of which are currently met by the current system. Types and levels of unmet needs vary across age and the care continuum. This study aimed to identify the shared and unique supportive care needs of younger and older GC patients and survivors to inform improved supportive care. Nineteen younger and ten older women, 3 months to 5 years post a GC diagnosis, were purposively recruited during active treatment, and at early and extended survivorship. Audiotaped and transcribed semi‐structured interviews were thematically analysed to establish areas of needs. GC patients reported nine shared needs relating to support, isolation, uncertainty, information, asking questions, escape from illness, advocacy, loss and finding meaning. Younger patients reported unique needs related to the impact of treatment‐induced menopause. There is a need for a systematic screening process to identify women who require and want additional help, to ensure appropriate and timely assistance or referrals are provided. Identification of needs will allow health professionals to provide relevant and timely information and support services, resulting in improved quality of life for women affected by GC.